PEMBIASAAN BUDAYA 5S SEBAGAI UPAYA UNTUK MENINGKATKAN SIKAP DISIPLIN SISWA DI SMP NEGERI 13 SEMARANG - Zakyatin Nufus, Noni; Wahono, Margi (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study is driven by the concern over students' low level of discipline, as evidenced by a lack of compliance with school rules and a weak awareness of responsibilities. One way to improve discipline is to implement habits of smiling, greeting, greeting, being polite, and being courteous in everyday life in the school environment. This study aims to determine the effect of this cultural habit on students' disciplinary attitudes. The method used is a quantitative approach with a correlational design. Data were collected by distributing questionnaires to ninth-grade students selected using a simple random sampling technique. The obtained data were then analyzed using descriptive analysis, assumption testing, and simple linear regression analysis to determine the relationship between variables. The results show that the habit of smiling, greeting, greeting, being polite, and being courteous has a positive and significant influence on students' disciplinary attitudes. The level of relationship between the two variables is in the very strong category, and the high contribution of influence indicates that this habit plays a significant role in shaping disciplinary behavior. Thus, it can be concluded that the consistent implementation of a positive culture in the school environment can increase students' awareness and compliance with applicable rules